Analisis Ukuran Droplet pada Partially-Hydrogenated Biodiesel Minyak Jelantah - Valerie, I N. G. A.; Wirawan, I K. G.; Ghurri, A. (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract Waste cooking oil (WCO) biodiesel is a promising alternative energy to anticipate environmental problems and the limited availability of fossil fuels. In an effort to improve its oxidation stability, a controlled method called partial hydrogenation was carried out. Changes in physical properties due to the partial hydrogenation process will affect the atomization ability of the fuel. The droplet size measurements test was carried out using diesel fuel (D100), waste cooking oil biodiesel (B100), a mixture of diesel 90%–biodiesel 10% v/v (B10), a mixture of diesel 80%–biodiesel 20% v/v (B20), a mixture of diesel 70%–biodiesel 30% v/v (B30), partially-hydrogenated (PH) waste cooking oil biodiesel, a mixture of diesel 90%–biodiesel PH 10% v/v (D90PH10), a mixture of diesel 80%–biodiesel PH 20% v/v (D80PH20), and a mixture of diesel 70%–biodiesel PH 30% v/v (D70PH30) at various injector pressures of 2000 psi, 2500 psi, and 3000 psi. The test results show that PH biodiesel fuel has a smaller average droplet size than non-PH biodiesel along with the addition of pressure variations. Keywords: Biodiesel, partial hydrogenation, droplet size